ІННОВАЦІЙНЕ ОСВІТНЄ СЕРЕДОВИЩЕ ЯК ФАКТОР РОЗВИТКУ ОСОБИСТОСТІ (Педагогіка вищої та середньої школи, 2007)
The article deals with the pedagogical technology of formation of theory functional educational environment as a way of providing général educational institution. Its influence on the child’s personal development is researched.